Respuesta :

Step-by-step explanation:

Enter a problem...

Algebra Examples

Popular Problems

 

Algebra

 

Expand using the Binomial Theorem (3x+2)^4

(3x+2)4(3x+2)4

Use the binomial expansion theorem to find each term. The binomial theorem states (a+b)n=n∑k=0nCk⋅(an−kbk)(a+b)n=∑k=0n⁡nCk⋅(an-kbk).

4∑k=04!(4−k)!k!⋅(3x)4−k⋅(2)k∑k=04⁡4!(4-k)!k!⋅(3x)4-k⋅(2)k

Expand the summation.

4!(4−0)!0!⋅(3x)4−0⋅(2)0+4!(4−1)!1!⋅(3x)4−1⋅(2)+4!(4−2)!2!⋅(3x)4−2⋅(2)2+4!(4−3)!3!⋅(3x)4−3⋅(2)3+4!(4−4)!4!⋅(3x)4−4⋅(2)44!(4-0)!0!⋅(3x)4-0⋅(2)0+4!(4-1)!1!⋅(3x)4-1⋅(2)+4!(4-2)!2!⋅(3x)4-2⋅(2)2+4!(4-3)!3!⋅(3x)4-3⋅(2)3+4!(4-4)!4!⋅(3x)4-4⋅(2)4

Simplify the exponents for each term of the expansion.

1⋅(3x)4⋅(2)0+4

Hope this helps!

Answer:81x^4+216x^3+216x^2+96x+16

Step-by-step explanation:cause yussss

ACCESS MORE